A comparative study of three different methods of shoot meristem excision for induction of embryogenic calli in coconut - U, Bhavyashree; K, Lakshmi Jayaraj; TP, Fayas; KS, Muralikrishna; KK, Sajini; MK, RAJESH; Karun, Anitha (Research in Biotechnology, 2016)
A protocol was standardized to maximize yields of embryogenic calli from shoot meristem culture of coconut. Three different shoot meristem excision methods were tested viz., excision of shoot meristem aseptically from in vitro germinated embryo after 10-12 days, excision of shoot meristem from in vitro germinated embryo subjected to GA3 treatment for five days and excision of shoot meristem from fresh embryo. The primary calli induction after 30 days of culture incubation for the three treatments were 21%, 27%Â and 79% respectively. Â Further, the primary calli formed from the shoot meristem excised from fresh embryo gave rise to 56% of embryogenic calli. The calli obtained from the shoot meristem which were excised from in vitro germinated embryo formed less percentage of embryogenic calli because of the presence of cotyledonary tissues which inhibited the multiplication of meristematic tissues. In the case of shoot meristem extracted from GA3-treated embryos, the percentage of non-embryogenic calli was more compared to the shoot meristem excised from fresh embryo. It was observed that the addition of GA3 in the initial stages of culture inhibited the formation of embryogenic calli and favored direct shoot development. Currently, the shoot meristem excised from fresh embryo is being employed for scaling up the planting material production from released varieties of coconut.